2003
DOI: 10.1016/s0002-9440(10)64318-0
|View full text |Cite
|
Sign up to set email alerts
|

Matrilysin (Matrix Metalloproteinase-7) Mediates E-Cadherin Ectodomain Shedding in Injured Lung Epithelium

Abstract: Matrilysin (matrix metalloproteinase-7) is highly expressed in lungs of patients with pulmonary fibrosis and other conditions associated with airway and alveolar injury. Although matrilysin is required for closure of epithelial wounds ex vivo, the mechanism of its action in repair is unknown. We demonstrate that matrilysin mediates shedding of E-cadherin ectodomain from injured lung epithelium both in vitro and in vivo. In alveolar-like epithelial cells, transfection of activated matrilysin resulted in sheddin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
264
0
4

Year Published

2006
2006
2012
2012

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 288 publications
(280 citation statements)
references
References 50 publications
11
264
0
4
Order By: Relevance
“…23 Specifically, MMP-7 could facilitate epithelial cell migration by losing cell-cell and cell-matrix contacts. 24 To understand the biological significance of the cirrhosis-associated MMP-7 polymorphism on cell motility, a wound-healing assay was applied. HSC-T6-MMP7(Asp) cells migrated significantly faster than the HSC-T6-MMP7(Gly) and control HSC-T6-NC cells at 24 hours after wounding (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Specifically, MMP-7 could facilitate epithelial cell migration by losing cell-cell and cell-matrix contacts. 24 To understand the biological significance of the cirrhosis-associated MMP-7 polymorphism on cell motility, a wound-healing assay was applied. HSC-T6-MMP7(Asp) cells migrated significantly faster than the HSC-T6-MMP7(Gly) and control HSC-T6-NC cells at 24 hours after wounding (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Migration of resident HSCs is believed to be critical for the progression of liver fibrosis because it accounts for the increased numbers of activated HSCs in areas of injury. 29 Moreover, MMP-7 is able to cleave ECM and basement membrane, 30 and mediate E-cadherin ectodomain shedding in injured lung epithelium, 24 leading to accelerated cell migration. In this study, the wound healing and Boyden chamber assays demonstrated that HSC-T6 cells expressing MMP-7(Asp-137) variant acquired an enhanced migratory capacity as compared with cells expressing MMP-7(Gly-137) (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In a complex tissue environment, like cancer, several cell types (resident, inflammatory, tumor) express several, different MMPs, and these proteinase can either promote or restrain disease or repair processes by affecting multiple and apparently opposing processes by the same cell at the same time (Coussens et al, 2002;Egeblad and Werb, 2002;Parks et al, 2004). For example, we have determined that epithelial MMP-7 is required for wound closure and generation of antimicrobial activity (Dunsmore et al, 1998;Wilson et al, 1999) (clearly beneficial functions), but it also promotes neutrophil activation, which can be damaging and lethal McGuire et al, 2003). It is likely that to effect on different processes at the same time, a cell uses distinct mechanisms to compartmentalize an MMP to different substrates.…”
Section: Significancementioning
confidence: 97%
“…Epithelial cells at the edges of wounded tracheal explants migrate towards each other and fuse. MMP7 seems to mediate wound-induced epithelial migration by cleaving E-cadherin 84 . MMP7 colocalizes with E-cadherin and cleaves its extracellular domain in wounded epithelia, which results in a loosening of cell-cell attachments.…”
Section: Mmp7 Is Involved In Innate Immunity and Wound Healingmentioning
confidence: 99%